Multifunctional landscapes identification and associated development zoning in mountainous area - Peng, Jian; Hui, Xiaoxu; Qiu, Sijing; Hu, Yi'na; Meersmans, Jeroen; Liu, Yanxu (Elsevier, 2019)
Multifunctional landscape has become a new discipline growth point in landscape ecology. Globally mountainous areas occupy about one fifth of Earth's surface. However, few studies focused on landscape multifunctionality in mountainous areas. Taking Dali Bai Autonomous Prefecture, China, as a case study area, five typical landscape functions (net primary productivity, soil retention, water yield, crop production, and residential support) were quantified and mapped. Hotspots of multiple landscape functions were identified using spatial overlap tools, interaction between each landscape function pair was discussed through Spearman's rank correlation analysis, and development zoning was conducted based on landscape function bundle. The results showed that, about 61% of the study area had at least one kind of landscape function hotspot, with only 2.7% covering three or more kinds of landscape function hotspots. Significant trade-offs or synergies existed between all pairs of landscape functions, except the pair of net primary productivity and residential support. With the application of Self-Organizing Feature Maps (SOFM) method, the study area was divided into four types of development zones (i.e. ecological shelter area, ecological transition area, suburban development area, and urban agglomeration area) which were all corresponding to different landscape function bundles. This study could provide spatial guidance for differentiated sustainable developing in mountainous areas according to local conditions of landscape multifunctionality.
Keywords: Multifunctional landscape; Synergies and trade-offs; Northwestern Yunnan; Development zoning